Slideshare uses cookies to improve functionality and performance, and to provide you with relevant advertising. If you continue browsing the site, you agree to the use of cookies on this website. See our User Agreement and Privacy Policy.

Slideshare uses cookies to improve functionality and performance, and to provide you with relevant advertising. If you continue browsing the site, you agree to the use of cookies on this website. See our Privacy Policy and User Agreement for details.

Successfully reported this slideshow.

Like this presentation? Why not share!

- Chapter 3: Roots of Equations by Maria Fernanda 9180 views
- Sum and product of roots by Majesty Ortiz 3296 views
- Quadratic equations by Anup Mahato 58341 views
- nature of the roots and discriminant by maricel mas 2185 views
- ROOTS OF EQUATIONS by Kt Silva 3868 views
- Newton Raphson Of Root Equation by ShirishChaudhari 458 views

19,625 views

Published on

No Downloads

Total views

19,625

On SlideShare

0

From Embeds

0

Number of Embeds

8

Shares

0

Downloads

208

Comments

0

Likes

2

No embeds

No notes for slide

- 1. Investigating the relationships between the roots and the coefficients of quadratic equations. T- 1-855-694-8886 Email- info@iTutor.com By iTutor.com
- 2. Solve each of the following quadratic equations a) x2 + 7x + 12 = 0 b) x2 – 5x + 6 = 0 c) x2 + x – 20 = 0 d) 2x2 – 5x – 3 = 0 Write down the sum of the roots and the product of the roots. Roots of polynomial equations are usually denoted by Greek letters. For a quadratic equation we use alpha (α) & beta (β)
- 3. ax2 + bx + c = 0 a(x - α)(x - β) = 0 a = 0 This gives the identity ax2 + bx + c = a(x - α)(x - β) Multiplying out ax2 + bx + c = a(x2 – αx – βx + αβ) = ax2 – aαx – aβx + aαβ = ax2 – ax(α + β) + aαβ Equating coefficients b = – a(α + β) c = aαβ -b/a = α + β c/a = αβ
- 4. Use the quadratic formula to prove the results from the previous slide. -b/a = α + β c/a = αβ a acbb 2 42 a acbb 2 42 a b a b a acbb a acbb 2 2 2 4 2 4 22 a c a ac a acbb a acbb a acbb 22 2222 4 4 4 )4( 2 4 2 4
- 5. Find a quadratic equation with roots 2 & -5 -b/a = α + β c/a = αβ -b/a = 2 + -5 c/a = -5 2 -b/a = -3 c/a = -10 Taking a = 1 gives b = 3 & c = -10 So x2 + 3x – 10 = 0 Note: There are infinitely many solutions to this problem. Taking a = 2 would lead to the equation 2x2 + 6x – 20 = 0 Taking a = 1 gives us the easiest solution. If b and c are fractions you might like to pick an appropriate value for a.
- 6. The roots of the equation 3x2 – 10x – 8 = 0 are α & β 1 – Find the values of α + β and αβ. α + β = -b/a = 10/3 αβ = c/a = -8/3 2 – Find the quadratic equation with roots 3α and 3β. The sum of the new roots is 3α + 3β = 3(α + β) = 3 10/3 = 10 The product of the new roots is 9αβ = -24 From this we get that 10 = -b/a & -24 = c/a Taking a = 1 gives b = -10 & c = -24 So the equation is x2 – 10x – 24 = 0
- 7. 3 – Find the quadratic equation with roots α + 2 and β + 2 The sum of the new roots is α + β + 4 = 10/3 + 4 = 22/3 The product of the new roots is (α + 2)(β + 2) = αβ + 2α + 2β + 4 = αβ + 2(α + β) + 4 = -8/3 + 2(10/3) + 4 = 8 So 22/3 = -b/a & 8 = c/a To get rid of the fraction let a = 3, so b = -22 & c = 24 The equation is 3x2 – 22x + 24 = 0
- 8. The roots of the equation x2 – 7x + 15 = 0 are α and β. Find the quadratic equation with roots α2 and β2 α + β = 7 & αβ = 15 (α + β)2 = 49 & α2β2 = 225 α2 + 2αβ + β2 = 49 α2 + 30 + β2 = 49 α2 + β2 = 19 So the equation is x2 – 19x + 225 = 0
- 9. Call us for more information: www.iTutor.com 1-855-694-8886 Visit

No public clipboards found for this slide

×
### Save the most important slides with Clipping

Clipping is a handy way to collect and organize the most important slides from a presentation. You can keep your great finds in clipboards organized around topics.

Be the first to comment